STRATEGI PEMBELAJARAN KOLABORATIF GURU DALAM MENGEMBANGKAN LITERASI DAN KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR - Andi Saadillah; Rahma Mawadda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Literacy and speaking skills are important competencies that need to be developed from elementary school onwards. However, in reality, there are still students who do not read actively, lack confidence in expressing their opinions, and have limited opportunities to interact in learning activities. Collaborative learning is one approach that can be used to overcome these problems by emphasizing cooperation among students in learning groups. This study describes how teachers apply collaborative learning strategies to develop students' literacy and speaking skills in elementary school. This study uses a qualitative approach with a descriptive method. Data were obtained through observation techniques, interviews with sixth-grade Indonesian language teachers at the Ihya As-Sunnah Wundulako Islamic Boarding School, and literature studies. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that collaborative learning strategies are implemented through group work activities, group discussions, presentations of discussion results, and peer feedback. Teachers also encourage less active students to participate in presentations to boost their confidence in speaking. In addition, the use of simple technological media such as audio devices and projectors helps improve students' attention and understanding of the learning material. In practice, teachers face challenges in managing time and student engagement, but collaborative learning has been proven to transform the learning atmosphere to be more active and improve students' reading literacy and speaking skills.